2017
DOI: 10.5664/jcsm.6848
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of Small Fiber Pathways in Primary Restless Legs Syndrome: Aδ Pathway Study

Abstract: On the basis of the analysis of LEPs and their comparison with the respective results from the control group, the presence of functional disability of the thermonociceptive Aδ pathway was confirmed in patients with primary RLS. The results indicated the presence of changes in the conduction of small fiber pathways in the pathomechanism of idiopathic RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Fila et al [84] using laser evoked potentials (LEP) (this method examines small fibre evoked potentials by rapidly delivering short and narrow pulses of noxious laser stimulus) showed normal latencies and amplitude in the upper limbs but increased latency of N2 in both lower limbs and of P2 in the right lower limb in RLS patients. Compared with controls, RLS patients showed a significantly higher thermo‐nociceptive threshold in both upper and lower limbs, increased N2 and P2 latencies in the feet, and increased P2 amplitude both in the hands and in the feet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fila et al [84] using laser evoked potentials (LEP) (this method examines small fibre evoked potentials by rapidly delivering short and narrow pulses of noxious laser stimulus) showed normal latencies and amplitude in the upper limbs but increased latency of N2 in both lower limbs and of P2 in the right lower limb in RLS patients. Compared with controls, RLS patients showed a significantly higher thermo‐nociceptive threshold in both upper and lower limbs, increased N2 and P2 latencies in the feet, and increased P2 amplitude both in the hands and in the feet.…”
Section: Resultsmentioning
confidence: 99%
“…The normality of QNART [20] and QSART [82] in patients with iRLS suggests that alterations in QTST found in patients with this condition should not be related to small sensory fibre dysfunction, whereas the abnormalities of SSR found in patients with iRLS in another study suggest the opposite [83]. Studies with LEP were consistent both with central and peripheral sensory dysfunction in patients with RLS [84]. Finally, studies with CPT showed data consisting of fluctuating small and large fibre dysfunction [85,86].…”
Section: Discussionmentioning
confidence: 99%
“…There are only few previous LEP studies performed in RLS patients reporting overall normal responses to nociceptive fibers stimulation. 16,17,33 However, RLS patients were examined only during the day, with a single study demonstrating comparable LEPs value between patients and controls, but increased values from daytime to nighttime in the patients. 17 Fila and colleagues 16 found prolonged latency and increased amplitude of LEPs recorded in lower limbs of RLS, an apparently conflicting neurophysiological result.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,33 However, RLS patients were examined only during the day, with a single study demonstrating comparable LEPs value between patients and controls, but increased values from daytime to nighttime in the patients. 17 Fila and colleagues 16 found prolonged latency and increased amplitude of LEPs recorded in lower limbs of RLS, an apparently conflicting neurophysiological result. In neuropathic patients, a prolonged N2 latency is consistent with impairment of Aδ fibers conduction, and patients with abnormal latencies generally disclose a reduction of the mean N2-P2 amplitude, which likely reflects an associated length-dependent loss of Aδ fibers because of a secondary axonopathy 34 or temporal desynchronization of the cortical potential caused by the Aδ fibers demyelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation